PENGARUH PENDAPATAN DAN JUMLAH TANGGUNGAN KELUARGA TERHADAP PENGELUARAN KONSUMSI RUMAH TANGGA - Rahmi, Rahmi; Septiani, Indri; Sari, A. Ratna (Patria Artha Journal of Accounting dan Financial Reporting, 2022)
This study aims to determine the effect of income and number of dependents on household consumption expenditures. The population in this study were community customers who received direct cash assistance (BLT) totaling 91 people. The sampling technique in this study was non-random sampling, where the researcher took a sample of part of the total population. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis using multiple linear analysis methods. The results based on this path analysis show that income has an insignificant effect on household consumption expenditures, the number of family dependents has a significant effect on household consumption expenditures receiving direct cash assistance and the income and number of family dependents simultaneously has a significant effect on household consumption expenditures receiving direct assistance cash.